Self-rotating 3D chiral mechanical metamaterials. (28th July 2021) - Dudek, K. K.; Drzewiński, A.; Kadic, M.
Abstract : In this work, we demonstrate that three-dimensional chiral mechanical metamaterials are able to self-twist and control their global rotation. We also discuss the possibility of adjusting the extent of the global rotation manifested by the system in a programmable manner. In addition, we show that the effect of the global rotation can be observed both for small systems composed of a single structural unit as well as more complex structures incorporating several structural elements connected to each other. Finally, it is discussed that the results presented in this work are very promising from the point of view of potential applications such as satellites or telescopes in space, where appropriately designed mechanical metamaterials could be used for the attitude control as well as other systems where the control of the rotational motion is required.